(untitled) (Research, Society and Development, 2022)
This article aims to provide the existing tools to face the struggle for human rights and public policies for the lesbian, gay, bisexual and transvestite (LGBT) population, listing how challenging their implementation is. Also bringing the rescue of one of the actions that are already being developed in the search for these rights, focusing on the health area. For this, a historical retrospective was made since the invention of the unified health system (SUS), a health system that should serve the entire population without distinction, however, it is not about the reality faced, so that it is necessary to have that LGBT people are also part of the “all” in question. The objective of the study was to deal with public policies in Brazil for the LGBT community, from the perspective of the need for more robust and effective laws aimed at the LGBT public in the field of public health, through the concept of equity, and using the mechanism of Human Rights. Humans. Thus, it was mentioned the actions that the Executive Branch, with the support of the Judiciary, can take to correct these distortions. As a result, it is concluded that the difficulties encountered by the LGBT population collide with the strong rejection of the Legislative Power, which, dominated by conservative and non-partisan benches, prevents any social advance for the LGBT population from becoming legal recognition through laws that, directly or indirectly benefit this part of society.